ASSET MANAGEMENT SYSTEM DESIGN OF VILLAGE BASED ON GEOGRAPHIC INFORMATION SYSTEM - Heri Suhendar; Joko Iskandar; Dede Kurniadi; Yosep Septiana (Jurnal Teknik Informatika (Jutif), 2022)
Management of an asset by the government is a process that starts from planning to asset inventorying that have been pre-existing or obtained from legitimate assistance so that they can managed appropriately and beneficially for the community. For the government, especially in village regions, management of assets is very important, so that both government apparatus and village community get complete, accurate and real-time information about the assets owned by the village government so that the information can be used for activities of village government and communities optimally. The goal of this research is to design and build an asset management system based on geographic information system (GIS) for government in the village. The GIS-based asset management design system uses a waterfall-model approach with five stages, namely: 1) Analysis, 2) Design, 3) Implementation, 4) Integration Testing, and 5) Maintenance. This asset management application is built with web-based technology using the Leaflet framework that supports Web Map Service (WMS) layers, GeoJSON data, vectors and tile layers, while the database in this application uses MySQL. The results of this GIS-based asset management system design research can be used to store, collect, repair, process, control and monitoring assets so that asset management for activities that benefit the community can be optimally improved. For the maintenance and utilization of asset management applications, training is carried out for operators and supervisors, as well as system support personnel.